IEEE International Workshop on Intelligent Signal Processing, 2005.
DOI: 10.1109/wisp.2005.1531645
|View full text |Cite
|
Sign up to set email alerts
|

Domestic power consumption measurement and automatic home appliance detection

Abstract: The electronic power meter sensor module was developed as a part of a global intelligent management system for domestic power consumption management (TELEC) 1 for energy optimisation, both in terms of client costs and energy saving. Abs ract tThere is an increasing concern for the intelligent management of domestic power consumption based on intelligent sensors and actuators (attached to domestic appliances). This paper describes the electronic power meter sensor module of an intelligent management system bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 2 publications
0
18
0
Order By: Relevance
“…Numerous studies have identified the attributes of a solution to these issues: personalized, frequent, continuous, credible, clear and concise feedback that provides an appliance-specific breakdown of how energy is used in the home [5,19,7,1,11,13,15,38]. Field studies showed that with proper feedback, residential electricity and/or gas use could be reduced by up to 50% [14], although typical savings were in the 9%-20% range [42,20,45,1,47]. Improved feedback can also help curtail peak use by up to 50% [27,44].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have identified the attributes of a solution to these issues: personalized, frequent, continuous, credible, clear and concise feedback that provides an appliance-specific breakdown of how energy is used in the home [5,19,7,1,11,13,15,38]. Field studies showed that with proper feedback, residential electricity and/or gas use could be reduced by up to 50% [14], although typical savings were in the 9%-20% range [42,20,45,1,47]. Improved feedback can also help curtail peak use by up to 50% [27,44].…”
Section: Introductionmentioning
confidence: 99%
“…An example of energy monitoring system of the typical appliances in a home was presented by [19]. This proposed monitoring system presents a limited performance because only electrical appliances which were connected to the outlets could be measured, since the monitoring system could not access the lighting equipment, which represents an important part of the energy spent in many households.…”
Section: Decentralized Measurement Methodsmentioning
confidence: 99%
“…One is using single sensor to monitor the power outlet [21] or multiple sensor to measure the electrical information of individual appliance [27]. The major problem is that it requires special technical expertise for single sensor deployment or incurs huge expense for multiple sensor installation and maintenance.…”
Section: Appliance Detectionmentioning
confidence: 99%